Comparative analysis of blood routine, C-reactive protein, and biochemical markers in children with Mycoplasma pneumoniae pneumonia and its coinfections - Tang, Xingjia; Chen, Chongfeng (Frontiers in Pediatrics, 2025)
IntroductionMycoplasma pneumoniae pneumonia (MPP) is a common cause of pediatric community-acquired pneumonia, and coinfections with Haemophilus influenzae (Hi) or influenza virus may alter disease severity. Identifying distinct laboratory patterns may help clinicians recognise coinfections early.MethodsA retrospective analysis was conducted on 140 hospitalized children with confirmed MPP (2014–2024). Patients were grouped as MPP alone (n = 64), MPP+Hi (n = 36), and MPP+influenza (n = 40). Clinical characteristics, complete blood count (CBC), hypersensitive C-reactive protein (hs-CRP), and biochemical indicators (ALT, AST, CK, CK-MB, urea, creatinine) were compared among groups. Correlation analyses were performed for biochemical markers.ResultsChildren with MPP+Hi showed the highest hs-CRP levels (23.93 ± 21.26 mg/L), longest fever duration, and longest hospital stay. The MPP+influenza group had significantly lower WBC (7.25 ± 3.50 × 109/L) and platelet counts (266.00 ± 97.46 × 109/L), and a higher monocyte percentage (10.18 ± 3.29%). Simple MPP cases had the highest lymphocyte percentage. No group differences were found in ALT, AST, CK, CK-MB, urea, or creatinine, although CK-MB was elevated across all groups. Correlation analysis showed weak but significant associations among AST, ALT, CK, and CK-MB.ConclusionCoinfection type influenced inflammatory and haematological patterns in children with MPP: Hi coinfection produced stronger inflammatory responses, while influenza coinfection showed viral-associated lymphopenia and thrombocytopenia. Routine laboratory parameters may support earlier recognition of coinfections and guide more targeted clinical management.